2020
DOI: 10.1038/s41598-020-76821-9
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the diversity and composition of gut microbiota in pigeon squabs infected with Trichomonas gallinae

Abstract: Pigeons, as the only altricial birds in poultry, are the primary Trichomonas gallinae (T. gallinae) host. To study the effects of T. gallinae infection on gut microbiota, we compared the microbiota diversity and composition in gastrointestinal (GI) tracts of pigeons at the age of 14 and 21 day with different degrees of T. gallinae infection. Thirty-six nestling pigeons were divided into three groups: the healthy group, low-grade and high-grade trichomonosis group. Then, the crop, small intestine and rectum con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 71 publications
1
30
0
Order By: Relevance
“…The contents of Fe in the above grit samples were as high as 1.28 ± 0.7% ( Zhang et al, 2021 ), indicating that one reason might be the antagonism of high Fe concentration with Ca utilization. Another reason might be the ability of pigeon to obtain P from the degradation of dietary phytate by diverse microbial communities in the crop, which had the highest microbial diversity among GI tract ( Ji et al, 2020 ). Zeller et al (2016) reported a synergistic effect of intrinsic and supplied phytase in the crop of broilers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The contents of Fe in the above grit samples were as high as 1.28 ± 0.7% ( Zhang et al, 2021 ), indicating that one reason might be the antagonism of high Fe concentration with Ca utilization. Another reason might be the ability of pigeon to obtain P from the degradation of dietary phytate by diverse microbial communities in the crop, which had the highest microbial diversity among GI tract ( Ji et al, 2020 ). Zeller et al (2016) reported a synergistic effect of intrinsic and supplied phytase in the crop of broilers.…”
Section: Discussionmentioning
confidence: 99%
“…Some authors have suggested that phytate is hydrolysed by phytases produced by micro-organisms present in the small intestine and particularly in the ceca of broilers ( Leytem et al, 2008 ). Our trial has indicated that the microbiota diversity was higher in crop than in small intestine and rectum of healthy pigeons at 14 and 21 days old ( Ji et al, 2020 ). Therefore, the P metabolism and utilization in pigeons might be different from that in broilers.…”
Section: Introductionmentioning
confidence: 92%
“…As the main product of meat pigeon breeding, they have extremely high nutritional value and are known as “one pigeon is better than nine chickens” ( Xu et al, 2020 ). Thus, the pigeon squab is an important representative of high-quality animal products and the consumer demand for squabs is increasing ( Ji et al, 2020 ). However, the natural feeding mode by parent pigeons restricts the production efficiency of squabs, which has become a restrictive factor in the pursuit of maximum economic benefits.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we also observed that CAP administration enhanced the accumulation of T-β-MCA. The decrease of Lactobacillus abundance could lead to changing the intestinal environment dramatically, such as pH, and then the abundance of harmful bacteria appeared to increase (58). In this study, the genera abundances of Desulfovibrio were significantly increased in the CAP group.…”
Section: Discussionmentioning
confidence: 54%